DETERMINAN YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF - Yunida Haryanti (Dian Nuswantoro Semarang, 2018)
ABSTRACTExclusive breastfeeding is breastfeeding only to infants up to the age of 6 months without additional liquids or other foods. Based on the data coverage of exclusive breastfeeding in the Rahmawati by 80%, this shows there are still 20% that the baby is not exclusively breastfed. Efforts to improve breastfeeding is still lacking.This study aims to identify factors associated with exclusive breastfeeding which includes factors of knowledge, attitude, work, support health workers and support her husband. This type of research is analytic survey with cross sectional approach.Respondents in this study were mothers who have children aged 6-59 months amounted to 52 people and taken samples using total sampling. Collecting data using questionnaires and data analysis using Chi-Square.The results showed factors associated with exclusive breastfeeding ie knowledge (P value = 0.011), occupation (P value = 0.047), the support of health workers (P value = 0.019) and the support of her husband (P value of 0.006, while factors unrelated that is the attitude (P value = 0.067). To improve exclusive breastfeeding can improve the health centers health education services for mothers and their families about the mechanism of pumping mechanism and the role of families in supporting exclusive breastfeeding by the method of group discussions and home visits.Keywords: Exclusive Breastfeeding, Mothers, BabiesABSTRAK ASI eksklusif adalah pemberian ASI saja pada basyi sampai usia 6 bulan tanpa tambahan cairan ataupun makanan lain (Dewi, 2013). Berdasarkan data cakupan ASI eksklusif di BPS Rahmawati sebesar 80% hal ini menunjukkan masih 20 % bayi yang belum mendapatkan ASI eksklusif. Upaya meningkatkan pemberian ASI masih kurang. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang berhubungan dengan pemberian ASI eksklusif yang meliputi faktor pengetahuan, sikap, pekerjaan, dukungan petugas kesehatan dan dukungan suami. Jenis penelitian yang digunakan adalah survey analitik dengan pendekatan cross sectional. Responden dalam penelitian ini adalah ibu yang mempunyai bayi 7-12 bulan yang berjumlah 52 orang dan diambil dan sampel menggunakan total sampling. Pengumpulan data menggunakan kuesioner dan analisa data menggunakan Chi-Square. Hasil penelitian menunjukkan faktor-faktor yang berhubungan dengan pemberian ASI eksklusif yaitu pengetahuan (P value = 0,011), pekerjaan (P value = 0,047), dukungan petugas kesehatan (P value =0,019) dan dukungan suami (P value 0,006 sedangkan faktor yang tidak berhubungan yaitu sikap (P value = 0,067). Untuk meningkatkan pemberian ASI eksklusif puskesmas dapat meningkatkan pelayanan pendidikan kesehatan bagi ibu dan keluarganya tentang mekanisme mekanisme memompa ASI serta peranan keluarga dalam mendukung pemberian ASI esklusif dengan metode diskusi kelompok dan kunjungan kerumah.Kata Kunci: ASI Esklusif, Ibu dan Bayi